Early Onset Severe Hypertensive Disease in Pregnancy and Screening for Antiphospholipid Syndrome - Nasim C. Sobhani; Rachel Shulman; Erin E. Tran; Juan M. Gonzalez (Thieme Medical Publishers, Inc., 2020)
Objective Although preterm delivery (PTD) before 34 weeks for severe hypertensive disease is a diagnostic criterion for antiphospholipid syndrome (APS), there is no consensus regarding testing for antiphospholipid antibodies (aPL) in this setting. We aim to describe the frequency of and the characteristics associated with inpatient aPL testing in this population. Study Design In this retrospective study of PTD before 34 weeks for severe hypertensive disease, charts were reviewed for aPL testing, gestational age at delivery, fetal complications, and severity of maternal disease. Wilcoxon rank-sum test, Fisher's exact, and chi-squared tests were used for analyses of continuous and categorical variables, and multivariate logistic regression for adjusted odds ratios. Results Among 133 cases, 14.3% had APS screening via aPL testing. Screened patients delivered earlier than unscreened patients (28.9 vs. 31.7 weeks, p <0.001). Each additional week of gestation was associated with a 39% decrease in the odds of screening (95% confidence interval: 0.43-0.85). There were no other differences between the groups. Conclusion APS screening after PTD for severe hypertensive disease is uncommon but more likely with earlier PTD. Despite conflicting recommendations from professional organizations, prior studies demonstrate contraceptive, obstetrical, and long-term risks associated with APS, suggesting that we should increase our screening efforts.